Expression cloning in yeast of a cDNA encoding a broad specificity amino acid permease from Arabidopsis thaliana. - Frommer, W B (1993)
To study amino acid transport in plants at the molecular level, we have isolated an amino acid permease cDNA from Arabidopsis thaliana by complementation of a yeast mutant defective in proline uptake with a cDNA. The predicted polypeptide of 53 kDa is highly hydrophobic with 12 putative membrane-spanning regions and shows no significant homologies to other known transporters. Expression of the cDNA enables the yeast mutant to take up L-[14C]proline. Competition studies argue for a broad but stereospecific substrate recognition by the permease, which resembles neutral or general amino acid transport systems from Chlorella and higher plants. Both pH dependence and inhibition by protonophores are consistent with a proton symport mechanism.